2008
DOI: 10.2136/sssaj2007.0109
|View full text |Cite
|
Sign up to set email alerts
|

Water Treatment Residuals and Biosolids Coapplications Affect Semiarid Rangeland Phosphorus Cycling

Abstract: Land coapplication of water treatment residuals (WTR) with biosolids has not been extensively researched, but the limited studies performed suggest that WTR sorb excess biosolidsborne P. To understand the long-term effects of a single coapplication and the short-term impacts of a repeated coapplication on soil P inorganic and organic transformations, 7.5-by 15-m plots with treatments of three different WTR rates with a single biosolids rate (5, 10, and 21 Mg WTR ha −1 and 10 Mg biosolids ha −1 ) surface coappl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Most studies that evaluated the impacts of P‐source and WTR additions on soil soluble P concentrations have focused on laboratory incubations (Dayton et al, 2003; Novak and Watts, 2004; Agyin‐Birikorang and O'Connor, 2007), column leaching studies (Elliott et al, 2002b; O'Connor et al, 2002), or indoor rainfall simulation studies with packed boxes (Agyin‐Birikorang et al, 2007). Some studies have evaluated WTR effectiveness in controlling excess soil soluble P under field conditions (Dayton and Basta, 2005a; Novak and Watts, 2005; Agyin‐Birikorang et al, 2007; Bayley et al, 2008). However, these studies examined the extent of soluble P reductions in soils, and no attempt was made to directly assess P concentrations of ground water due to WTR land application.…”
mentioning
confidence: 99%
“…Most studies that evaluated the impacts of P‐source and WTR additions on soil soluble P concentrations have focused on laboratory incubations (Dayton et al, 2003; Novak and Watts, 2004; Agyin‐Birikorang and O'Connor, 2007), column leaching studies (Elliott et al, 2002b; O'Connor et al, 2002), or indoor rainfall simulation studies with packed boxes (Agyin‐Birikorang et al, 2007). Some studies have evaluated WTR effectiveness in controlling excess soil soluble P under field conditions (Dayton and Basta, 2005a; Novak and Watts, 2005; Agyin‐Birikorang et al, 2007; Bayley et al, 2008). However, these studies examined the extent of soluble P reductions in soils, and no attempt was made to directly assess P concentrations of ground water due to WTR land application.…”
mentioning
confidence: 99%
“…This amorphous alum results in very high specific surface area, enhancing binding kinetics (Lucas and Greenway, 2011a). This media amendment has proven effective in reducing interstitial phosphate (PO 4 ) concentrations in P‐enriched soils (Bayley et al, 2008). It is expected that as the freshness fades, the P binding capability of the amorphous alum will degrade significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Isotherm experiments were conducted to estimate the equilibrium amount of P adsorbed onto the media surface as a function of its concentration in aqueous phase at a constant temperature. Although mesocosm experiments can simulate P removal under different conditions, determining the idealized maximum P adsorption capacity by media is best estimated by using an adsorption isotherm (Atkins, 1978), such as those described by Freundlich or Langmuir models (Goldberg, 2005). These empirical isotherms can be used to estimate the relative P removal by bioretention blends because P equilibrium concentration levels are relatively low in urban runoff (Harter and Baker, 1977).…”
Section: Isotherm Experimentsmentioning
confidence: 99%
“…Greater P content in the occluded phase represents greater P within retaining components or minerals (Evans and Syers 1971). Bayley et al (2008) studied short-and long-term Al-WTR applications to a shortgrass steppe rangeland soil, showing that Al-WTR contributed to increased P content in the occluded phase as well as the soluble + Al + Fe-bound phase. The authors suggested that these fractions were relatively stable over the long term (e.g., decadal) and thus possibly would be stable in the current system studied.…”
Section: Inorganic P Fractionationmentioning
confidence: 99%